Про комунікативно-прагматичний потенціал апроксиматорів - Морєва, Галина Георгіївна; Moreva, G. G. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Мета статті – спроба дослідити комунікативно-прагматичний потенціал репрезентантів категорії при¬близності (апроксимації) – так званих апроксиматорів. Об’єктом дослідження виступають найбільш частотні апроксиматори французької мови presque, à peu près, environ у художній літературі. Наявність апроксиматора перед словом указує на його приблизну відповідність референту (Rx), яка не має знакового відображення (вна¬слідок своєї новизни або довільності), але ідентична за певними ознаками іншому референту (Rw), словесно відображеному в мові. Вибір мовцем того чи того апроксиматора не довільний, він диктується передусім їх семантикою, тісно пов’язаною з етимологією, яка полягає в різноспрямованості / односпрямованості приблиз¬ності, а також у ступені наближеності до точки відліку. Суттєвим також є тип мовної оцінки – раціональної (об’єктивної) або емоціональної (суб’єктивної). The aim of the research is to study the communicative and pragmatic potential of the representatives of the category of approximation – the so-called approximators. The aim has identified the following range of objectives of the research 1) to reveal the semantic nature of approximation; 2) to research approximators functioning at the level of speech production and speech recep¬tion; 3) to analyze the role of approximators as text forming factors. The object of the research is most frequent French approximators presque, à peu près, environ in fiction. The presence of an approximator before the word indicates its approximate correspondence to the referent (Rx), which has no sign representation (because of its novelty or derivativeness), but by certain indications it’s identical to another referent (Rw), which is verbally represented in the language. The choice of this or that approximator is not arbitrary, but it depends, in the first place, on semantics which is closely connected with etymology and lies in multidirectionality and unidirectionality of approximation and also in the extent of its closeness to the reference point. The type of language evaluation – rational (objective), that influences the mind of the hearer, or emotional (subjective), that influences his feelings, is significant.
Of the Communicative and Pragmatic Potential of Approximators
Keywords: категорія приблизності (апроксимації); category of approximation; апроксиматори; approximators; односпрямованість / різноспрямованість приблизності; multidirectionality / unidirectionality of approximation